PENGARUH PEMBELAJARAN BERDIFERENSIASI BERBANTUAN MATERI AJAR GEOMETRI BERBASIS RME TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS 3 SEKOLAH DASAR - Eksa Aqila Cindyana; Jesi Alexander Alim; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports a study that was conducted to obtain information objectively and to examine the differences in students’ mathematical reasoning skills who studied with the differentiated learning method assisted by RME-based geometry teaching materials with students who studied with conventional methods. The study used a quasi-experimental method with a non-equivalent control group design. The study was conducted in the academic year of 2021/2022 on geometry material in the mathematics learning subject. The subjects of the study involved the third-grade students of SD Madani Islamic School Riau which consisted of 3A as the control class and 3C as the experimental class. In conducting the study, data were collected through a pretest and a final test (posttest) that was provided to the experimental and the control classes, which consisted of 6 essay questions. The statistical data obtained were normality, homogeneity, and hypothesis testing, which were processed by using the SPSS 25 program. Based on the results of hypothesis testing, a significance value (2-tailed) was 0.029. Hence, the significance value was <0.05. Thus, it could be concluded that the result was an effect of RME-based geometry teaching materials-assisted differentiation learning on students’ mathematical reasoning skills at the third-grade students of SD Madani Islamic School Riau.